Safety profiles of anti-VEGF drugs: bevacizumab, ranibizumab, aflibercept and ziv-aflibercept on human retinal pigment epithelium cells in culture. (17th May 2014) - Malik, Deepika; Tarek, Mohamed; Caceres del Carpio, Javier; Ramirez, Claudio; Boyer, David; Kenney, M Cristina; Kuppermann, Baruch D
Abstract : Purpose: To compare the safety profiles of antivascular endothelial growth factor (VEGF) drugs ranibizumab, bevacizumab, aflibercept and ziv-aflibercept on retinal pigment epithelium cells in culture. Methods: Human retinal pigment epithelium cells (ARPE-19) were exposed for 24 h to four anti-VEGF drugs at 1/2×, 1×, 2× and 10× clinical concentrations. Cell viability and mitochondrial membrane potential assay were performed to evaluate early apoptotic changes and rate of overall cell death. Results: Cell viability decreased at 10× concentrations in bevacizumab (82.38%, p=0.0001), aflibercept (82.68%, p=0.0002) and ziv-aflibercept (77.25%, p<0.0001), but not at lower concentrations. However, no changes were seen in cell viability in ranibizumab-treated cells at all concentrations including 10×. Mitochondrial membrane potential was slightly decreased in 10× ranibizumab-treated cells (89.61%, p=0.0006) and 2× and 10× aflibercept-treated cells (88.76%, 81.46%; p<0.01, respectively). A larger reduction in mitochondrial membrane potential was seen at 1×, 2× and 10× concentrations of bevacizumab (86.53%, 74.38%, 66.67%; p<0.01) and ziv-aflibercept (73.50%, 64.83% and 49.65% p<0.01) suggestive of early apoptosis at lower doses, including the clinical doses. Conclusions: At clinical doses, neither ranibizumab nor aflibercept produced evidence of mitochondrial toxicity or cell death. However, bevacizumab and ziv-aflibercept showed mild mitochondrial toxicity at clinically relevant doses.